Psikoedukasi Pasangan Lansia dengan Hipertensi dan Ansietas - Yanti Apriyanti; Achir Yani S Hamid; Herni Susanti; Yossi Susanti Eka Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the implementation of psychoeducation in elderly couples with hypertension and anxiety. The research uses a case study approach in one family of elderly couples as clients and caregivers who experience hypertension and pressure. The instruments used were advanced mental assessment using the Stuart adaptation stress model approach and the Self-Reporting Questionnaire (SRQ)-20 to measure the ability and changes in the anxiety of elderly couples before and after family psychoeducation. Results: psychoeducation for elderly couples impacts increasing knowledge and ability to treat hypertension and pressure, and caregivers can manage stress and burden in the family. Conclusion: the application of family psychoeducation can be used to increase the knowledge and abilities of clients and caregivers in treating hypertension and anxiety for themselves and their family members. Keywords: Anxiety, Hypertension, Elderly, Psychoeducation